Comparison of the Burnout Levels of National Athletes According to Their Demographic Characteristics - Ahmet Uslu, Ünsal Tazegül (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There are many factors that affect the performance of athletes, burnout is one of them. Aim This study aims to compare the burnout levels of national athletes according to various variables.. Methods: The sample of the study consists of 432 athletes who voluntarily participated in the study. “Sport-Specific Multidimensional Perfectionism Scale” was used as a data collection tool in the study. SPSS 20 package program was used to analyze the data in this study. The “Kolmogorov-Smirnov” test was used to determine that the data had a normal distribution, and the “Anova-Homogenety of variance” test was used to determine its homogeneity, and it was determined that the data had a homogeneous and normal distribution. Descriptive statistics, Independent samples t-test and one-way analysis of variance were used in the analysis of the data. Results: At the end of the comparison of the scores according to the gender variable, a statistically significant difference was found in the dimension of Emotional-Physical Exhaustion (p <0.05). in other dimensions, no statistically significant difference was determined (p> 0.05). Conclusion: At the end of the statistical analysis, in the decreasing sense of accomplishment, It was determined that the female athletes had a high score in the emotional physical exhaustion dimension, and the male athletes had a high score in the depersonalization dimension.